Cancer-associated fibroblasts-derived CXCL12 enhances immune escape of bladder cancer through inhibiting P62-mediated autophagic degradation of PDL1 - Zhao Zhang; Yongbo Yu; Zhilei Zhang; Dan Li; Zhijuan Liang; Liping Wang; Yuanbin Chen; Ye Liang; Haitao Niu (Journal of Experimental & Clinical Cancer Research, 2023)
Abstract Background Cancer-associated fibroblasts (CAFs), the predominant stromal cell of tumor microenvironment (TME), play an important role in tumor progression and immunoregulation by remodeling extracellular matrix (ECM) and secreting cytokines. However, little is known about the details of the underlying mechanism in bladder cancer. Methods Bioinformatics analysis was performed to analyze the prognostic value of CAFs and CXCL12 using GEO, TCGA and SRA databases. The effects of CXCL12 on bladder cancer progression were investigated through in vitro and in vivo assays. The biological mechanism of the effect of CXCL12 on PDL1 were investigated using western blotting, immunoprecipitation, RT-PCR, immunofluorescence, mass spectrometry, protein stability, and flow cytometry. Results The results demonstrated that CAFs-derived CXCL12 promoted cancer cell migration and invasion and upregulated PDL1. Mechanistically, upon binding to its specific receptor, CXCL12 activated the downstream JAK2/STAT3 pathway and rapidly up-regulated the expression of deubiquitinase CYLD. CYLD deubiquitinated P62 causing P62 accumulation, which in turn inhibited the autophagic degradation of PDL1. In vivo experiments demonstrated that blocking CXCL12 inhibited tumor growth, reduced tumor PDL1 expression and increased immune cell infiltration. Conclusions This study revealed a novel mechanism for the role of CXCL12 in P62-mediated PDL1 autophagic regulation. Combined application of CXCL12 receptor blocker and PD1/PDL1 blocker can more effectively inhibit PDL1 expression and enhance antitumor immune response. Targeting CAFs-derived CXCL12 may provide an effective strategy for immunotherapy in bladder cancer.